The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/en15218079
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Short-Term Load Forecasting in Smart Grids

Abstract: A smart grid is the future vision of power systems that will be enabled by artificial intelligence (AI), big data, and the Internet of things (IoT), where digitalization is at the core of the energy sector transformation. However, smart grids require that energy managers become more concerned about the reliability and security of power systems. Therefore, energy planners use various methods and technologies to support the sustainable expansion of power systems, such as electricity demand forecasting models, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Existing studies demonstrated the effectiveness of DL-based models such as ANN, CNN, and LSTM compared to conventional ML-based algorithms [10,16]. RNN is a type of DL algorithm that utilizes feedback connection, enabling it to transfer information from one timestep to another.…”
Section: Model Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies demonstrated the effectiveness of DL-based models such as ANN, CNN, and LSTM compared to conventional ML-based algorithms [10,16]. RNN is a type of DL algorithm that utilizes feedback connection, enabling it to transfer information from one timestep to another.…”
Section: Model Architecturementioning
confidence: 99%
“…The ANN method demonstrated lower error (MAPE) and a regression factor (R) closer to 1, indicating superior performance compared to ARIMA. Ibrahim et al [16] utilized various ML and deep learning (DL) algorithms, including XG-Boost, AdaBoost, SVR, and ANN, for 24 h ahead predictions, with ANN exhibiting superior performance in terms of MAPE, RMSE, and R 2 , despite longer training times and higher computational expenses for DL algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…These problems are then addressed by many researchers, where we can mention [ 48 ], who presented a dynamic prediction of retail electricity prices in the Smart Grid based on the Stackelberg model. Then, [ 49 ], where the authors discuss the possibility of using ML and DL in refining the power generation forecast, and similarly [ 50 , 51 , 52 ] discuss the stability and security of the Smart Grid concerning short-term load. In conclusion, Smart Grids are rapidly replacing conventional grids on a global scale.…”
Section: Cyber Security In Substation Automation Systemsmentioning
confidence: 99%
“…Rewards that are given out after state transitions are used to address the convergence problem. The transition mechanism considers different device energy levels and deep learning methods to make the changes in energy consumptions [42][43][44]. Various schemes are proposed for perfect secret sharing mechanism in CRT [45].…”
Section: Related Workmentioning
confidence: 99%